(untitled) (NTU Journal of Engineering and Technology, 2026)
The research examined how sisal natural fibers combined with steel fibers with hooked ends influence the mechanical and physical properties of lightweight concrete. The lightweight quality of pumice made it a suitable alternative to regular aggregates, which supported environmental initiatives through insulation applications and partition panels. 70% of natural sand grains were substituted with fine and coarse pumice stock. The testing process separated the pumice into two fractions: the coarse elements stayed on the 12.5 mm screen while the fine pumice material fit through a 4.75 mm screen. Tensile and compressive strength evaluations were performed as well as flexural strength, modulus of elasticity, and dry density testing. The experimental samples included various volume combinations of sisal fibers at 0.25%, 0.5%, and 0.75% together with steel fibers at 1%, 1.25%, and 1.5% levels. The combination of sisal at 0.5% content delivered elevated tensile and flexural strength results, and performance declined due to increased porosity levels. 1.5% steel fibers exhibited the best performance in terms of compressive and flexural strength, which demonstrates their powerful reinforcement properties. Compressive strength decreased because sisal fibers did not bond well with the cement matrix and created additional holes inside the material. When 0.5% sisal particles were added to concrete instead of the standard mix, the tensile strength went up by 5.1% and the flexural strength went up by 7.8%. Concrete reinforced with 1.5% steel fibers showed strength gains of 10.5% and 26.9%, with minor decreases in workability and density. The experimental outcomes identified the best fiber-to-concrete ratio, offering an ideal combination of strength improvement and environmentally friendly practices in lightweight concrete.